Genomics of lung cancer - Fong, Kwun M.; Bowman, Rayleen V.; Yang, Ian A. (Journal of Thoracic Disease, 2017)
Multi-platform investigation of non-small cell lung cancer has the capability of discovering clinically important biological pathways involved in cancer development, progression, prognosis and response to treatment in patients with lung cancer. These two complementary publications from this productive research group describe genomic analyses of the two commonest subtypes of lung cancer: lung adenocarcinoma (LUAD) and lung squamous cell carcinoma (LUSC).